Efficacy and safety of cryoballoon ablation in the elderly: A multicenter study. (1st March 2019) - Heeger, Christian-Hendrik; Bellmann, Barbara; Fink, Thomas; Bohnen, Jan-Eric; Wissner, Erik; Wohlmuth, Peter; Rottner, Laura; Sohns, Christian; Tilz, Roland Richard; Mathew, Shibu; Reissmann, Bruno; Lemeš, Christine; et al.
Abstract: Background: The prevalence of atrial fibrillation (AF) increases with age. Second-generation cryoballoon (CB2)-based PVI has demonstrated encouraging clinical results in the treatment of paroxysmal (PAF) and persistent atrial fibrillation (PersAF). The objective of this study was to assess data on safety, efficacy and long-term clinical success of CB2-based pulmonary vein isolation (PVI) in patients ≥75 years of age. Methods: CB2-based PVI was performed in 104 patients ≥75 years of age (elderly group) and symptomatic AF (PersAF: n = 44, 42.3%) in three highly experienced German EP centers. The data was compared to propensity score matched patients with age <75 years ( n = 104, control group; PersAF: n = 45, 43.3%, p = 0.956). Results: The median age of the elderly group was 77.5 [75, 80] years while it was 63 [52, 70] years of control group patients ( p = 0.0001). The median procedure time was 92.5 [75, 120] minutes (elderly group) and 100 [75, 120] (control group), p = 0.124. Major complications were registered in 7/104 (6.7%) elderly patients and 7/104 (6.7%) control group patients ( p = 0.999). Clinical success in terms of freedom from AF recurrence after one-year follow-up was 80% (95% CI: 72–88) and 82% (95% CI: 75–90) and after three-year follow-up 59% (95% CI: 47–74) and 49% (95% CI: 37 64) for the elderly group and the control group, respectively ( p = 0.7). Conclusions: CB2-based PVI in patients ≥75 years of age appears safe, is associated with low procedure times and shows promising clinical success rates equal to patients of the younger population. Highlights: Second-generation cryoballoon (CB2)-based pulmonary vein isolation (PVI) has demonstrated encouraging clinical results in the treatment of atrial fibrillation. However, only limited data is available concerning outcomes of CB2-based PVI in elderly patients. The data provides evidence for equal safety and efficacy of CB2-based PVI in patients ≥75 years compared to patients of the younger age.